EFFECT OF TEMPERATURE AND STORAGE ON EFFECTIVENESS OF Trichoderma viride as BIOCONTROL AGENTS on Rigidoporus microporus, PATHOGEN of WHITE ROOT ON RUBBER - Nurhayati Damiri; Mulawarman Mulawarman; Mitra Mutiara (AGRIVITA, Journal of Agricultural Science, 2014)
This research was aimed to study the effect of temperature and storage on effectiveness of Trichoderma viride to suppress Rigidoporus microporus development, the pathogen of white root disease on rubber.  This research applied a randomized complete block design with five treatments and five replications. Each treatment contained two rubber plants (total of plants 50).  There were five treatments i.e.: compost containing T.  viride which was stored at 17oC for a month ( A ),  compost containing T.  viride  which was  stored at 24oC  for a month ( B ),  compost containing T.  viride which was stored at 30oC for a month (C), Triadimefon ( D) and R. microporus  ( control Results showed that that T. viride compost which was stored for a month at various temperatures was able to suppress R.  microporus development. Trichoderma viride compost which was stored at of 17o C for a month showed the best result. It was was able to supress white root disease severity up to 70 percent and rhizomorph colonization up to 62 percent respectively.  The treatment was also able to increase the plant height and stem diameters. Keywords: effectiveness, Rigidoporus micro-porus, storage duration, temperature, Trichoderma viride